A válogatás . The Selection - Gyula, Gazdag (Hungary, 1970)
CEU Arts and Culture Program - donation Duration: 00:40:00 The KISZ group (Communist Youth Organization) of a factory in Hungary announces a competition call to recruit an in-house music band which would entertain as well as guide its young members. The initially simple procedure however gets more and more intricate as the ideological requirements amass. The camera follows the project from the beginning to the end as the initial enthusiasm drowns into rules, regulations and ideological restrictions.